Nanotechnological approach to delivering nutraceuticals as promising drug candidates for the treatment of atherosclerosis. (1st January 2021) - Pillai, Sindhu C.; Borah, Ankita; Jacob, Eden Mariam; Kumar, D. Sakthi
Abstract: Atherosclerosis is Caesar's sword, which poses a huge risk to the present generation. Understanding the atherosclerotic disease cycle would allow ensuring improved diagnosis, better care, and treatment. Unfortunately, a highly effective and safe way of treating atherosclerosis in the medical community remains a continuous challenge. Conventional treatments have shown considerable success, but have some adverse effects on the human body. Natural derived medications or nutraceuticals have gained immense popularity in the treatment of atherosclerosis due to their decreased side effects and toxicity-related issues. In hindsight, the contribution of nutraceuticals in imparting enhanced clinical efficacy against atherosclerosis warrants more experimental evidence. On the other hand, nanotechnology and drug delivery systems (DDS) have revolutionized the way therapeutics are performed and researchers have been constantly exploring the positive effects that DDS brings to the field of therapeutic techniques. It could be as exciting as ever to apply nano-mediated delivery of nutraceuticals as an additional strategy to target the atherosclerotic sites boasting high therapeutic efficiency of the nutraceuticals and fewer side effects.